Effect of physical training on lung function and respiratory muscles strength in policewomen trainees - Awad, Kamal M.; Magzoub, Aamir; Elbedri, Omer; Musa, Omer (International Journal of Research in Medical Sciences, 2017)
Background: Measurement of respiratory muscles strength has not been widely investigated in the context of physical training. Methods: This cross-sectional study has assessed pulmonary function and strength of respiratory muscles in two women groups: group I includes healthy policewomen (n=28) exposed to physical training 3 hours daily for at least 2 years and group II is a matched control group (n=31) of untrained apparently healthy second year medical students. Lung function tests including forced vital capacity (FVC), forced expiratory volume in the first second (FEV1) and peak expiratory flow rate (PEF) were performed using a digital spirometer and maximum inspiratory and expiratory pressures (MIP and MEP) as indicators for respiratory muscle strength were measured using a digital respiratory pressure meter. Results: The mean FVC (L), FEV1 (L), PEF (L/min) values were significantly higher in the police-trained group (p=0.000, 0.000 and 0.003 respectively). Similarly, the mean MIP and MEP (cm/H2O) values were significantly higher among trained group (p=0.000 and 0.003 respectively). Conclusions: Long-term regular physical exercise improves lung function as well as respiratory muscle power and may delay the age-related decline in lung function.